Discursos generados por usuarios en publicaciones de Facebook sobre expresiones calificadas como “racistas” realizadas por personajes mediáticos: Julieta Rodríguez, Ivana Yturbe y Antonio Pavón - Cáceres, Ana (2021)
This research analyzed the reactions of users on Facebook caused by the expres sions classified as racist mentioned by media characters on Peruvian television. In Peru, media personalities are widely popular and make constant appearances on television, exposing their personal lives constantly. These appearances usually have bounces published through the profiles of national newspapers on digital platforms such as Facebook; where, finally, users generate a speech about what happened. Previously, no research has been carried out on the subject in Peru, so the gap is found in the lack of studies located at the national level and that focus on the media characters exposed on open television and how this is transferred to a virtual space such as Facebook. The methodology that was developed for the research was mixed. For the first part, a qualitative technique was applied, in which a content and context analysis was used as a tool on the racist comments issued by the media characters. For the second part, a quantitative technique was applied, in which the observation and data collection was used as a tool, for which a Facebook post was selected for each case exposed and comments were classified and taken into account the reac tions made by users of the social network. As main findings, the expressions used by Rodriguez, Yturbe and Pavón were classified as racist, since not only the words they said were considered, but also the rhythm, diction and speed of voice when expressing themselves. In addition, a majority trend was obtained in the ‘annoyed’ and ‘derogatory’ comments by users on Facebook against the media personalities that are part of the show business. On the other hand, and to a lesser extent, were the comments “in favor” showing support for public figures and “impartial”.